Pengembangan Modul Pembelajaran Ipa Berbasis Contextual Teaching And Learning (CTL) Untuk Siswa Kelas V di SDN 197 Pulau Pekan - Soniyah Oktarisma; Firman Firman; Desyandri Desyandri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This study aims to develop a science learning module based on Contextual Teaching and Learning (CTL) for class V at SDN 197 / II Pulau Pekan. The type of research used is development (Research and Development) using a 3-D modification model which consists of the determining stage, the design stage, and the development stage. This research was conducted in the odd semester of the 2021/2022 school year. The validator questionnaire consists of 1 design validator lecturer and 1 lecturer as validator material. Based on the research, the module validation resulted from the display aspect of the Science module based on Contextual Teaching and Learning (CTL) obtained a value of 92.5% and from the material aspects obtained from 93%, and seen from the average score of the Natural Science learning table based on Contextual Teaching and Learning (CTL) that was obtained as a whole was 93% in the very valid category. While the practicality test consisted of 1 teacher and 22 students. From the results of the practicality of the teacher with the proportion of results of 92.5% and from the results of the practicality of the students, the proportion of results was 85%. From the results of this study, it can be seen that the resulting Contextual Teaching and Learning (CTL)-based science learning module is very valid and practical to use in science learning. So that it can be used in science learning in grade V SD.